Komunikasi Persuasif pada Community Development (Kajian Tematik Perspektif Al-Qur’an) - Arfiani, Anindya Septiana (BINA' AL-UMMAH, 2022)
Poverty is almost always a major problem in a country, because it becomes one of the causes of gaps that often lead to comflik. The truth is Qur'an has offered the concept of Integrated Development which is able to be one of the solutions to poverty alleviation. Then how communication becomes so important in the framework of the realization of community development. Starting from that problem, this research will discuss how persuasive communication in the framework of community development becomes important in view of the perspective of the Qur'an, as well as how Allah SWT showed a successful development success through the leadership of the Prophet Muhammad PBUHThis research uses qualitative descriptive studies with a library study approach that collects and records sources from relevant scientific books and journals. The result of this study is that persuasive communication is designed to change the audience so that the development program runs sustainsble and organic. This concept was used and exemplified by the Prophet when building the people of Medina through his prophetic communication.